The Influence of Organizational Culture and Providing Incentives on Employee Performance - Novita, Lola; Syahril; Gistituati, Nurhizrah; Sabandi, Ahmad (LPPM Undiksha, 2023)
This research is motivated by the author's observations regarding the problem of low employee performance at the Office of Education and Culture of the City which shows that organizational culture and incentives are still not in accordance with what is expected and employee performance is still not optimal. The purpose of this study was to analyze positive influence of organizational culture and the provision of incentives on employee performance at the Education and Culture Office of the City. This research is a correlational quantitative research with associative type. The population in this study was all employees at the Office of Education and Culture of the City totaling 90 employees and the sample was determined using the Cohran formula with an error rate of 10% with the Proportionate Stratified Random Sampling technique obtained 63 employees. The research instrument uses a questionnaire with a Liker scale which has 5 alternative answers. Before the questionnaire was used, trials were carried out to determine its validity and reliability. Data analysis techniques were performed using multiple linear regression tests which were processed using SPSS version 24. The results of the data analysis show that there is a significant influence between organizational culture and the provision of incentives jointly on employee performance. So the multiple linear regression equation used is 32.864+0.324X1+0.427X2+e. In the determination coefficient test, the gain is r² = 0.613 which shows that the determination of the organizational culture variable and the provision of incentives on employee performance is 61.3%.